PENGARUH MEDIA TANAM DAN NUTRISI AB MIX TERHADAP PERTUMBUHAN DAN HASILKAILAN (Brassica oleraceaL.) SECARA WICK SISTEM HIDROPONIK - Yuyun Yunengsih; Armaini Armaini; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Hydroponics wick system using AB Mix in some media of planting is expected capable of generating growth and power results of plant crocheted. The research aims to obtain a variety of planting media and the concentration of the best AB mix nutrients for the growth of kailan plants, conducted at the UPT Faculty of Agriculture, University of Riau, from April 2019 to May 2019. Research in the form of 3x4 factorial experiment with Complete Random Design.Consists of 3 types of growing medium, huskchorcoal, cocopeat, sawdust while the nutrient solution consists of AB mix concentrations of 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm. The parameters observed, height plant, number of leaves, length of leaves, width of leaves, long roots, the diameter of the rod, fresh weight per plant, weight suitable for consumption per plant. Planting medium charcoal husk on the concentration of nutrients 1000 ppm resulted in the growth of plants kailan were good. Keywords: Hydroponics, growing medium and Nutrition AB mix